Characterization and antimicrobial properties of fluorine-rich carbon films deposited on poly(lactic acid) - Boonyawan D. (2014)
This study describes the effect of fluorine contents on the properties of carbon films deposited on poly(lactic acid) (PLA) substrate using plasma enhanced chemical vapor deposition (PECVD) technique. A mixture of acetylene (C2H2) and carbon tetrafluoride (CF4) gas was utilized for film deposition. The thickness of the deposited carbon film was in the range of 150-350nm. The film's deposition rate was found to increase with the decreasing CF4 concentration in the gas mixture. Fourier transform spectroscopy revealed the presence of C-F bonds, and X-ray photoelectron spectroscopy showed that the C-C bonds of the carbon film were replaced by the C-CFx bonds. This affirms that the films have a polymer-like structure. High concentration of fluorine (up to 25at.%) could be obtained when 50% of CF4 was used. PLA coated with F-rich carbon film showed hydrophobic character due to the formation of -CFx bonds. The film with a high concentration of fluorine showed excellent performance on reduction of Escherichia coli (E. coli) growth. © 2011 Elsevier B.V.